2017
DOI: 10.1108/ijchm-09-2015-0491
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impacts and certification: evidence from the Milan World Expo 2015

Abstract: Purpose-This study examines residents' perceptions of environmental impacts and certification for the Milan World Expo 2015 as well as their overall attitude towards the mega event. Design/methodology/approach-A survey of Milan residents based on a convenience sample of residents in Milan led to 221 useable questionnaires. Findings-Residents perceived that the Expo will have minimal negative and positive environmental impacts. A minority of residents were aware of the environmental certification of the event. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 74 publications
1
23
0
Order By: Relevance
“…Certification programs and tourism standards have become popular in recent years. In particular voluntary standards and eco-labels have introduced specific indicators that can foster socially, culturally and environmentally responsible tourism (Buckley, 2002; Dos Santos, Méxas and Meiriño, 2017; Honey, 2002; Guizzardi et al., 2017). However, despite the positive impact of sustainable certification on environmental protection, social integrity and economic viability of remote, or less popular destinations, the applicability of several standards to mature tourism areas has been strongly disputed (Margaryan and Stensland, 2017; Sasidharan et al., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Certification programs and tourism standards have become popular in recent years. In particular voluntary standards and eco-labels have introduced specific indicators that can foster socially, culturally and environmentally responsible tourism (Buckley, 2002; Dos Santos, Méxas and Meiriño, 2017; Honey, 2002; Guizzardi et al., 2017). However, despite the positive impact of sustainable certification on environmental protection, social integrity and economic viability of remote, or less popular destinations, the applicability of several standards to mature tourism areas has been strongly disputed (Margaryan and Stensland, 2017; Sasidharan et al., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…With proper procedures and policies in place, the negative environmental impact can be mitigated. A case in point is Expo 2015 in Milan which was the first host city to obtain ISO certification for adherence to sustainability best practices, verified by residents who confirmed that the event had had a minimal environmental impact on urban life (Guizzardi et al (2017). Dubai’s policy planners seem to have embedded environmental sustainability into policy-making, which is reflected in the thematic attribution for Expo 2020.…”
Section: Triple Bottom Line Impactmentioning
confidence: 98%
“…However, Hall (2012) warns managing and delivering events is not a solution to enhance competitiveness, instead researchers need to transcend neoliberal thinking when exploring impacts. Event impacts are always intended, but are not always clearly understood; interpretations can differ among stakeholders (Wallstam et al , 2020), especially resident populations (Doumi et al , 2020; Guizzardi et al , 2017). Lauermann (2019) notes residents will raise skepticism when impact or legacy plans are vague.…”
Section: Literature Reviewmentioning
confidence: 99%